Development of a Financial Behavior Model of Buy Now Pay Later Users: The Role of Lifestyle, Overconfidence, and Debt Knowledge - Abdul Rahman Laba; Rusnawati Rusnawati (Journal of Entrepreneur, Business and Management, 2026)
AbstractThe growth of Buy Now Pay Later (BNPL) services, better known as paylater, has changed the consumption patterns of students in online shopping in Makassar City. The ease of transactions offered often leads students to spend without considering their ability to repay, thus triggering debt behavior. This study aims to develop a financial behavior model of BNPL users by examining the role of lifestyle and overconfidence on debt behavior, as well as the role of debt knowledge as a moderating variable. The study used a quantitative approach with primary data collected through questionnaires. The sampling technique used a non-probability sampling type of purposive sampling with a sample size calculated based on the Hair Formula, resulting in 120 student respondents using the paylater feature. Data analysis was conducted using a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS. The results showed that lifestyle and overconfidence each had a positive and significant effect on debt behavior. Debt knowledge was shown to significantly moderate the effect of lifestyle on debt behavior, but not significantly in moderating the effect of overconfidence on debt behavior. The developed model is able to explain 66.2% of the variation in debt behavior of BNPL users, so it can be a reference for students, educational institutions, and BNPL service providers in designing debt literacy education.Keywords: Buy Now Pay Later; Lifestyle; Overconfidence; Debt Behavior; Debt Knowledge